(untitled) (Revista de Ciências Agroveterinárias, 2005)
The study of probability of maximum air temperature for ten days periods is very useful to determine the better sowing times for annual crops. The objectives of this study were to develop equations to estimate annual standard deviation (parameter of normal distribution) and to generate maps with the probability of maximum air temperature for ten days periods in Santa Catarina State, Brazil. The probability of maximum air temperature for ten days periods can be estimated according to the altitude, latitude and longitude in Santa Catarina. There were significant differences in the probability of maximum air temperature for ten days periods in different regions of the State.